Calibrating Spectral Decomposition of Local Earthquakes Using Borehole Seismic Records—Results for the 1992 Big Bear Aftershocks in Southern California. Issue 3 (8th March 2021) - Shearer, Peter M.; Abercrombie, Rachel E.
Abstract: Empirical approaches are often used to correct earthquake spectra for path effects in order to estimate corner frequencies and stress drops, but suffer from tradeoffs among source parameters and the shape of the empirical correction or Green's function. This hampers absolute stress‐drop estimates and comparisons between different studies or regions. Borehole records are less affected by site and attenuation effects than surface seismometers and thus provide more direct constraints on source spectra. We analyze 1, 787 earthquakes of the 1992 to 1993 Big Bear aftershock sequence in southern California, which were recorded by both the Southern California Seismic Network (SCSN) and the Cajon Pass borehole seismometer at 2.5‐km depth. Spectral decomposition of P‐waves recorded by the SCSN yields source terms that can be fit equally well by a variety of models, owing to tradeoffs between the model parameters and the empirical correction term. Earthquake spectra recorded by the Cajon Pass borehole are consistent with a P‐wave Q of about 1, 000. For 25 Big Bear earthquakes in common, we find the correction spectrum that brings the event terms from spectral decomposition and the Q ‐corrected borehole spectra into best‐fitting agreement. This provides absolute calibration for the SCSN spectral decomposition results, which can then be used to process all the Big Bear earthquakes and estimate earthquake source properties without the parameter tradeoffs normally associated with the EGF approach. Our results highlight the limits of purely empirical approaches to spectral analysis for earthquake source properties and the importance of determining crustal attenuation models. Key Points: Empirical approaches to resolve earthquake source spectra suffer from large uncertainties in the absence of a crustal attenuation model The Cajon Pass borehole seismometer is less affected by attenuation than surface records and provides good constraints on source spectra Cajon Pass data are used to calibrate surface records of the 1992 Big Bear aftershocks, reducing the uncertainties in stress drop estimates